Isolation and pathogenicity of Streptococcus iniae in cultured red hybrid tilapia in Malaysia - Rahmatullah, Muhammad; Ariff, M.; Kahieshesfandiari, M.; Mohd Daud, Hassan; Saad, Mohd Zamri; Mohd Yusoff, Md Sabri; Azmai, Mohammad Noor Amal; Md Yasin, Ina Salwany (American Fisheries Society, 2017)
This study describes the isolation and pathogenicity of Streptococcus iniae in cultured red hybrid tilapia (Nile Tilapia Oreochromis niloticus × Mozambique Tilapia O. mossambicus) in Malaysia. The isolated gram-positive S. iniae appeared punctiform, transparently white, catalase and oxidase negative and produced complete β-hemolysis on blood agar, while a PCR assay resulted in the amplification of the 16 S rRNA gene and lactate oxidase encoded genes. The isolate was sensitive to tetracycline, vancomycin, and bacitracin but was resistant to streptomycin, ampicillin, penicillin, and erythromycin. Pathogenicity trials conducted in local red hybrid tilapia (mean ± SE = 20.00 ± 0.45 g) showed 90.0, 96.7, and 100.0% mortality within 14 d postinfection following intraperitoneal exposure to 104, 106, and 108 CFU/mL of the pathogen, respectively. The clinical signs included erratic swimming, lethargy, and inappetance at 6 h postinfection, while mortality was recorded at less than 24 h postinfection in all infected groups. The LD50-336 h of S. iniae against the red hybrid tilapia was 102 CFU/mL. The post mortem examinations revealed congested livers, kidneys, and spleens of the infected fish. This is the first report of S. iniae experimental infection in cultured red hybrid tilapia in Malaysia.